Propagation characteristics of autofocusing Airy beam with power exponential phase vortex in weak anisotropic oceanic turbulence. Issue 19 (11th November 2021) - Wang, Junzhe; Wang, Xinguang; Peng, Qin; Zhao, Shengmei
Abstract : In the paper, we present the analytical expression of propagation characteristics of the autofocusing Airy beam (AAB) with power-exponent-phase beam carrying orbital angular momentum (OAM) mode (named AAB-PEPV), in weak anisotropic oceanic turbulence. We discuss the influence of the weak oceanic turbulence on the detection probability of the AAB-PEPV beams with different power phases and wavelengths. The results show that the AAB-PEPV beam has a higher detection probability when the anisotropic ocean turbulence has a larger unit mass fluid dynamic energy dissipation rate, a larger internal ratio factor and a higher anisotropy factor. At the same time, the detection probability decreases with the temperature change dissipation rate, the temperature and salinity contribution to the refractive index spectrum. Additionally, for a larger power exponential phase and a longer wavelength, the AAB-PEPV beam has a better anti-interference performance in the underwater channel.